Respuesta :

Space

Answer:

p = -8

Step-by-step explanation:

Step 1: Write equation

7(p + 3) + 9 = 5(p - 2) - 3p

Step 2: Solve for p

  1. Distribute: 7p + 21 + 9 = 5p - 10 - 3p
  2. Combine like terms: 7p + 30 = 2p - 10
  3. Subtract 2p on both sides: 5p + 30 = -10
  4. Subtract 30 on both sides: 5p = -40
  5. Divide both sides by 5: p = -8

Step 3: Check

Plug in x to verify it's a solution.

  1. Substitute: 7(-8 + 3) + 9 = 5(-8 - 2) - 3(-8)
  2. Parenthesis: 7(-5) + 9 = 5(-10) + 24
  3. Multiply: -35 + 9 = -50 + 24
  4. Add: -26 = -26
ACCESS MORE
ACCESS MORE
ACCESS MORE
ACCESS MORE